PENGARUH PENGGUNAAN AIR KELAPA (Cocos nucifera) TERHADAP PERTUMBUHAN TANAMAN SAWI (Brassica juncea L.) - Riny R Tiwery (Program Studi Pendidikan Biologi FKIP Unpatti, 2014)
Background: The research purpose is to know the influences use of coconut water on the growth of mustard plants. The materials used on this research are: Green Mustard Seed, Coconut Water, Water and Soil. Research carried out for 2 months, from 15 September 2010 till 15 November 2010. Method: The research using Design Randomly Complette, that consist of 5 treatments with each treatments: A0 = control without coconut water, A1 = volume of coconut water is 100 ml, A2 = volume of coconut water is 150 ml, A3 = volume of coconut water is 200 ml, and A4 = volume of coconut water is 250 ml. Each treatments repeated 3 times. Data were analyzed using Analysis of Variance and followed by the Smallest Real Test at level α 0,5% and α 0,1%. Result: The result of the researchshowed that, the use of coconut water give a real impact on the growth of mustard plants on it’s height and number of leaves, that obtained on treatments A4 = volume of coconut water is 250 ml. Conclusion: The volume of coconut water that most influence on the growth of mustard (Brassica juncea L.), on plant height and number of leaves, contained in a volume of 250 ml, followed by volume of 200 ml, 150 ml and a further volume of 100 ml, and Control (A0).